Analysis of work processes of parts cleaning by immersion - Zhilenko, D. (Запоріжжя : ТДАТУ, 2025)
During operation, equipment is exposed to significant contamination, which complicates further operation of the machines, reduces their reliability and efficiency, and causes accelerated wear of component connections, corrosion, and aging of component materials.Immersion units are the main equipment of repair companies for cleaning parts from strong asphalt-resin deposits that are difficult to remove. The principle of operation of immersion equipment, the main technological element of which is a bath with a washing solution, is to use the ability of solutions to clean repair objects from dirt by destroying adhesive bonds.
Keywords: cleaning by immersion; intensification process; mechanical activators